The asparagine-transamidosome from Helicobacter pylori: a dual-kinetic mode in non-discriminating aspartyl-tRNA synthetase safeguards the genetic code - Fischer, Frédéric (Oxford University Press, 2012)
Helicobacter pylori catalyzes Asn-tRNA(Asn) formation by use of the indirect pathway that involves charging of Asp onto tRNA(Asn) by a non-discriminating aspartyl-tRNA synthetase (ND-AspRS), followed by conversion of the mischarged Asp into Asn by the GatCAB amidotransferase. We show that the partners of asparaginylation assemble into a dynamic Asn-transamidosome, which uses a different strategy than the Gln-transamidosome to prevent the release of the mischarged aminoacyl-tRNA intermediate. The complex is described by gel-filtration, dynamic light scattering and kinetic measurements. Two strategies for asparaginylation are shown: (i) tRNA(Asn) binds GatCAB first, allowing aminoacylation and immediate transamidation once ND-AspRS joins the complex; (ii) tRNA(Asn) is bound by ND-AspRS which releases the Asp-tRNA(Asn) product much slower than the cognate Asp-tRNA(Asp); this kinetic peculiarity allows GatCAB to bind and transamidate Asp-tRNA(Asn) before its release by the ND-AspRS. These results are discussed in the context of the interrelation between the Asn and Gln-transamidosomes which use the same GatCAB in H. pylori, and shed light on a kinetic mechanism that ensures faithful codon reassignment for Asn.